PARENTAL BONDING AND RELIGIUSITY ON PREMARITAL SEXUAL BEHAVIOR IN ADOLESCENTS DATING - Zahara Safitri (Psikoislamedia : Jurnal Psikologi, 2023)
In adolescence, thoughts and feelings about sexuality begin to emerge along with experiencing first love, having friends who are sexually active, and curiosity about sexuality begins to increase. One of the factors that influence premarital sexual behavior in adolescents is the weak attachment of adolescents to their parents (parental bonding) and the level of religiosity. The purpose of this study was to empirically examine the effect of parental bonding and religiosity on premarital sexual behavior in dating adolescents. This study involved 100 participants. Multiple regression analysis is used to test the hypothesis in this study. The results showed that parental bonding had an effect on premarital sexual behavior, while religiosity had no effect on premarital sexual behavior. The R2 value is 0.247, explaining that 24.7% of the variables of premarital sexual behavior in dating adolescents can be explained by parental bonding and religiosity variables, while the remaining 75.3% is influenced by other factors outside the study with a value of Sig. 0.000 (Sig. < 0.05).